The characterization of a mammalian DNA structure-specific endonuclease. - Harrington, J J (1994)
The repair of some types of DNA double-strand breaks is thought to proceed through DNA flap structure intermediates. A DNA flap is a bifurcated structure composed of double-stranded DNA and a displaced single-strand. To identify DNA flap cleaving activities in mammalian nuclear extracts, we created an assay utilizing a synthetic DNA flap substrate. This assay has allowed the first purification of a mammalian DNA structure-specific nuclease. The enzyme described here, flap endonuclease-1 (FEN-1), cleaves DNA flap strands that terminate with a 5' single-stranded end. As expected for an enzyme which functions in double-strand break repair flap resolution, FEN-1 cleavage is flap strand-specific and independent of flap strand length. Furthermore, efficient flap cleavage requires the presence of the entire flap structure. Substrates missing one strand are not cleaved by FEN-1. Other branch structures, including Holliday junctions, are also not cleaved by FEN-1. In addition to endonuclease activity, FEN-1 has a 5'-3' exonuclease activity which is specific for double-stranded DNA. The endo- and exonuclease activities of FEN-1 are discussed in the context of DNA replication, recombination and repair.